Analysis on ASEAN and European Union Policies Regarding Covid-19 - Shanti Darmastuti; Mansur Juned; Sophiana Widiastutie (Budapest International Research and Critics University, 2021)
COVID-19 has impacted multiple sectors of life. Experts believe that regional cooperation is a key effort that should be done to deal the COVID-19 pandemic. Regional cooperation starts with common interests among parties and provides benefits for every country involved in it. This article provides an overview of the socio-economic impact of COVID-19 as well as a comparison of the forms of regional cooperation carried out by Association of Southeast Asian Nations (ASEAN) and the European Union (EU) in responding COVID-19. This study uses literature studies in data collection. From the results of several studies that have been carried out before, both regions chose to conduct cooperation in the health and economic fields to respond to COVID-19. ASEAN's response in responding to the pandemic can be seen stronger in the principles of partnership that have been established with several partner countries. In addition, the principle of solidarity, exchange of information, knowledge, as well as strengthening institutional cooperation in ASEAN itself is an important point in the regional cooperation carried out. On the other hand, in addition to cooperation in the health sector, EU focuses on financial instruments among its collaborative approaches in the availability of aid packages to banking actors and institutions. The package of assistance provided by the EU to avoid market distortions and revive economic sectors is provided through the provision of credit and liquidity.